EFFECTIVENESS OF COMPUTER LEARNING MODEL GAMES AGAINST EARLY CHILDHOOD COGNITIVE DEVELOPMENT SCOPE OF DEVELOPMENT OF CONCEPTS OF SHAPES, COLORS AND SIZES - Rullyana, Gema; Masitoh, Masitoh; Riyana, Cepi (Prodi Teknologi Pendidikan, 2018)
Abstract. The general problem in this study is